Modeling Risk Management for Resources and Environment in China - Wu, Desheng Dash; Zhou, Yong (Computational Risk Management, 2191-1436, 2011)
This edited volume expands the scope of risk management beyond finance to include resources and environment issues in China. It presents the state-of-the-art approaches of using risk management to effectively manage resources and environment. Both case studies and theoretical methodologies are discussed.